PUBLIC PERCEPTIONS OF THE THE SOCIAL SECURITY AGENCY (BPJS) IN KENAGARIAN PAUH SUBDISTRICT DISTRICT LUBUK SIKAPING PASAMAN - Febrian, Kiki - (STKIP PGRI Sumbar, 2014)
The objective was to obtain and analyze the data or in-depth information about PublicPerceptions of the Social Security Agency (BPJS) in Pauh village Lubuk Sikaping districtPasaman region terms of: 1) services, 2) the work ethic, and 3) working hours.The research is a qualitative, of informants drawn by purposive sampling techniqueconsisting of a public of participants who become informants PBJS and the key is the employee /Social Security Agency staff Lubuk Sikaping district, Health Office staff Pasaman and partiesassociated with the implementation of Administering Agency. The data analysis techniques withdata reduction, data presentation and conclusion.The results showed: 1) Public perception of the services provided by the Social SecurityAgency (BPJS) in Pauh village Lubuk Sikaping district Pasaman region to the community is stilllacking, because the maintenance of the card and when people are willing to seek treatment, mashsociety must find its own drugs to pharmacies outside, (2) public perception of the work ethic theSocial Security Agency (BPJS) for people in Pauh village Lubuk Sikaping district Pasaman regionincluding either because the officer has the ability, knowledge of precision and accuracy in workand (3) public perception of working hours Administering Agency Social security for people inPauh village Lubuk Sikaping district Pasaman region included both as working 8 hours in 5working days, and the people are quite satisfied with working hours so that people feel BPJSofficers have certainty when having to deal with office BPJS